Assessment of Hearing During the Early Years of the American Otological Society. (April 2018) - Fitzgerald, Matthew B.; Jackler, Robert K.
Abstract : Objective: To describe the manner in which hearing was evaluated in American Otological Practice during the late 19th and early 20th centuries before introduction of the electric audiometer. Methods: Primary sources were the Transactions of the American Otological Society and American textbooks, especially those authored by Presidents of the Society. Results: In the era before electric audiometry multiple methods were used for evaluating the thresholds of different frequencies. Tuning forks were important for lower frequencies, whisper, and speech for mid-frequencies, and Galton's whistle and Konig's rod evaluated high frequencies. Hearing threshold was often recorded as in terms of duration of a sound, or distance from the source, rather than intensity. Hearing ability was often recorded a fraction, for example, with the distance a watch tick could be heard over the distance of a normal hearing individual. A variety of devices, such as Politzer's Acoumeter, attempted to deliver sound in a calibrated manner, thus enhancing the accuracy and reproducibility of test results. Conclusion: The early years of the American Otological Society were marked by a number of ingenious efforts to standardize hearing assessment despite the technical limitations. These efforts facilitated the development of the audiometer, and continue to influence clinical practice even today.